Collaborations: The Architecture of Ahrends, Burton and Koralek (ABK) edited by Kenneth Powell - Noble, Jonathan; Raman, Pattabi (Acta Structilia, 2004)
This article on one of the enduring British partnerships is not a vanity publication that we are accustomed to in our profession. Edited by Kenneth Powell, it contains illuminating essays of overlapping themes. The editor provides the overview. Jeremy Melvin writes a sensitive piece on the formation of the practice. While Elain Harwood and Frank Macdonald respectively describe early works and Irish projects of the practice Paul Finch contributes an intelligent essay on collaboration. The essays are not presented in succession but in layered colour strips on the top and bottom of pages with images in the body under the thematic titles of private/public, context, light/space and process. One does have to overcome the initial irritation of this unconventional layout before realising the importance of the ABK story. Indeed the interlocking of different narratives and the images has a resonance with the character of the practice itself, with three distinct personalities of Ahrends, Burton and Koralek, each with unique but complementary interests and predilections.